2010
DOI: 10.1080/15427560.2010.507409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Affective Reactions on Investment Decisions

Abstract: The present research aims to show how investors' affective reactions toward a fund influence their decision to sell the investment. Participants were presented with either a socially responsible or a traditional fund. After completing a mental images task, participants were asked to state the price at which they were willing to sell the fund and their confidence in future positive performance. Participants were willing to sell the fund at different prices depending on their affective reactions. The affective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
0
32
1
Order By: Relevance
“…Their social values matter when they make an investment (Diouf et al ., ), as do their social identity (Bauer and Smeets, ) and their social conscience (Perez‐Gladish et al ., ). The investor's reasoning has been investigated with respect to ethical frameworks (Viviers et al ., ), psychological processes (Bénabou and Tirole, ; Rubaltelli et al ., ) and behavioural influences (Glac, ; Bilbao‐Terol et al ., ; Pilaj, ).…”
Section: Emerging Themesmentioning
confidence: 99%
“…Their social values matter when they make an investment (Diouf et al ., ), as do their social identity (Bauer and Smeets, ) and their social conscience (Perez‐Gladish et al ., ). The investor's reasoning has been investigated with respect to ethical frameworks (Viviers et al ., ), psychological processes (Bénabou and Tirole, ; Rubaltelli et al ., ) and behavioural influences (Glac, ; Bilbao‐Terol et al ., ; Pilaj, ).…”
Section: Emerging Themesmentioning
confidence: 99%
“…In a somewhat similar vein, Tetlock [39] found that very high or very low levels of a Pessimism Factor predicted high trading volume in the Dow. Rubaltelli, Pasini, Rumiati, Olsen, and Slovic [119] likewise found that extreme levels of pleasant and unpleasant moods (but not moderate mood levels) led to the selling of losing funds. Although we do not know the mood activation levels in these prior studies, it might be the case that such activation played a role in the reported results.…”
Section: Discussionmentioning
confidence: 91%
“…Its establishment as a separate study can be said to have happened organically based on mounting empirical evidence gathered in studies on financial markets that contributed to contesting the "efficient markets hypothesis" underlying modern finance theory, which has cemented the notion of the market as an efficient, "near-perfect allocational device" ( [79], p. 377). Such evidence includes amongst others observations of investors practicing satisficing rather than optimising [80], the use of intuition and emotions in investment decision making [81], an impact of investor mood on stock markets [82] as well as an underestimation of risk and excessive trading [83], which also leads to a lack of diversification [84] and herding behaviour [85].…”
Section: What Is Behavioural Finance?mentioning
confidence: 99%